Living matter : the preservation of biological materials in contemporary art : an international conference held in Mexico City, June 3-5, 2019 - Rivenc, Rachel; Roth, Kendra (Getty Conservation Institute, 2022)
"This is the first book to provide a comprehensive overview of the conservation of biological materials used in contemporary art"--